Use of levothyroxine in the management of hypothyroidism: A historical perspective - Kahaly, George J.; Gottwald-Hostalek, Ulrike (Frontiers in Endocrinology, 2022)
The thyroid operates within a complex system of homeostatic regulation, where the level of thyrotropin (TSH) influences the rate of secretion of the principal thyroid hormones, thyroxine (T4) and triiodothyronine (T3). The devastating consequences of untreated thyroid dysfunction have been evident for centuries. Indeed, sources from antiquity described goitre and cretinism, two of the clinical sequelae of untreated overt thyroid disease. It was not until the first part of the 19th century that goitre and cretinism were first associated with iodine status; however, the endocrine function of the thyroid was not identified clearly until the early part of the 20th century. Three principal innovations in the 20th century supported the use of levothyroxine (LT4) replacement therapy for the management of hypothyroidism: a practical technique for the synthesis of LT4 suitable to support pharmaceutical use (late 1940s), the discovery that LT4 is converted to the active thyroid hormone, T3, in the peripheral tissues (1970), and the development of robust and sensitive assay methodology for measuring thyroid hormones in the blood (1960 onwards). Synthetic LT4, titrated to bring the level of TSH within a predefined “normal” reference range, is now established as the mainstay of treatment for hypothyroidism, and provides adequate restoration of thyroid hormone function for most people with this condition. Future research will explore further the nuances of the hypothalamic-pituitary-thyroid axis, and the place, if any for T3 within the management of thyroid dysfunction.